Investigation of Content Validity and Exploratory Factor Analysis of Students’ Economic Behavior Measure - Narmaditya, Bagus Shandy; Sahid, Sheerad; Hussin, Muhammad (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2024)
Economic behavior has attracted scholars in the last decade, and past studies measured this construct partially from consumptive perspectives or entrepreneurial behavior (Mulyani et al., 2018). Therefore, this study aims to develop a new and valid measurement of students’ economic behavior and investigate its content validity using an exploratory factor analysis (EFA). The content validity is provided using an experts’ assessment method with a 4-point evaluation form. At the same time, the exploratory factor analysis is performed using SPSS. This study involved content validity assessment for each item (I-CVI) for the entire scale (S-CVI/Ave). Based on the analysis of the questionnaire scale, it can be concluded that the content validity check using I-CVI, S-CVI/Ave, and S-CVI/UA is all satisfactory except for item SEB20, which was subsequently dropped. On the other hand, the results of EFA indicated that two more items did not meet the thresholds and, thus, were excluded. Therefore, developing instruments to measure students’ economic behavior is prominent in dealing with digital changes, preventing consumptive behavior, and enhancing economic well-being.